2017
DOI: 10.1007/s11738-017-2577-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TIBA, fluridone and salicylic acid on somatic embryogenesis and endogenous hormone and sugar contents in the tree fern Cyathea delgadii Sternb.

Abstract: Somatic embryogenesis (SE) in the tree fern Cyathea delgadii was first described in 2015 and since then has been used to exploration of this phenomenon in cryptogamic plants. To deepen the knowledge about the hormonal control of SE, stipe explants were cultured on media supplemented with hormone biosynthesis and transport inhibitors (HBTIs). In the presence of 30 µM 2,3,5-triiodobenzoic acid (TIBA), or 40 µM fluridone or 125 µM salicylic acid (SA), somatic embryo production was totally inhibited. The quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 55 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…The basis for the induction of SE in C. delgadii is an appropriate hormonal balance in explant cells established by etiolation of donor plantlets (Grzyb et al 2017). We also improved the current understanding of physiological and molecular processes involved in the induction and expression of early SE in this species (Grzyb et al 2018;Domżalska et al 2017). Our previous achievements have been summarised in the latest review article (Mikuła et al 2018).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The basis for the induction of SE in C. delgadii is an appropriate hormonal balance in explant cells established by etiolation of donor plantlets (Grzyb et al 2017). We also improved the current understanding of physiological and molecular processes involved in the induction and expression of early SE in this species (Grzyb et al 2018;Domżalska et al 2017). Our previous achievements have been summarised in the latest review article (Mikuła et al 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Although SE has been successfully achieved in numerous species of seed plants, only a few published reports describe this phenomenon in monilophytes, and all these studies were performed on the tree fern Cyathea delgadii Sternb. (Mikuła et al 2015a, b;Domżalska et al 2017;Grzyb et al 2017Grzyb et al , 2018. These investigations demonstrated that somatic embryos of C. delgadii are formed directly from single epidermal cells.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Understanding the physiological and molecular mechanisms by which the induction (direct or indirect) of SE occurs is a crucial step for its manipulation (Grzyb et al, 2018). Several factors can induce SE.…”
Section: Factors That Induce Somatic Embryogenesismentioning
confidence: 99%
“…Under stress conditions, MT promotes plant growth, delays senescence, and modulates photoperiod responses and root architecture [18]. MT may also protect plants against abiotic stressors such as heat [19], cold [20], salt [21], drought [22] and heavy metals [23]. MT augments plant stress tolerance by inducing the enzymatic detoxification of free radicals and reactive oxygen species (ROS) [24] and by scavenging excess ROS [2325].…”
Section: Introductionmentioning
confidence: 99%